Embrional tissue transplantation as a method of spinal cord recovery after experimental injury - Tsymbalyuk, V. I.; Chebotaryova, L. L.; Yaminskiy, Yu. Ya. (Ukrainian Neurosurgical Journal)
Experimental model of spinal cord contusion and method of spinal axons conduction study with electromyography in the rat are described. Our observation of movement recovery in plegic limbs and definition of spinal cord conduction in experimental rats allow to establish favorable terms for embrional tissue transplantation application after spinal cord injury.